Lymphangioma circumscriptum Associated with Port-Wine Stain - Shah, Nidhi; Rijal, A; Agrawal, S (Journal of BP Koirala Institute of Health Sciences, 2019)
Lymphangioma circumscriptum (LC) is a rare benign disorder involving the deep dermal and subcutaneous lymphatic channels. We present a case of a 32-year old 26 weeks pregnant female with multiple fluid filled vesicles over the vulvae of one year duration with itching. The lesions had increased in size after the onset of pregnancy. The patient also had a large port-wine stain (PWS) over the right buttock extending up to the perineum. The biopsy report was consistent with LC.